Cardiotoxicity after massive amantadine overdose - Schwartz, Michael D. (Springer-Verlag, 2008)
INTRODUCTION: Amantadine hydrochloride is an antiviral medication used as therapy for parkinsonism and as a cognitive enhancer. We report 2 cases of massive, acute ingestion of amantadine hydrochloride confirmed with serial serum levels. CASE REPORTS: A 47-year-old woman presented to the emergency department (ED) 30 minutes after ingesting 10 g of amantadine (150 mg/kg) by her report. Initial ECG revealed a sinus rhythm with rate of 93 bpm, and a QRS of 84 msec. While in the ED, the patient sustained a pulseless cardiac arrest and the monitor revealed ventricular tachycardia. She was successfully defibrillated. Postdefibrillation ECG showed a sinus rhythm (rate = 82 bpm), QRS of 236 msec, and QTc of 567 msec. The serum potassium was 1.0 mEq/L (1.0 mmol/L). The patient was given 300 ml (300 cc) 3% sodium chloride IV over 10 minutes. Ten minutes after completion of the hypertonic saline infusion, the patient’s ECG abnormalities resolved and the QRS was 88 msec. Her potassium was repleted over the next 11 hours postpresentation, and she also received an IV bolus of 4 g of magnesium sulfate immediately after the cardiac arrest. No further hypotension, dysrhythmia, conduction delay, or ectopy was noted during the patient’s hospital stay. The second case involved a 33-year-old female patient who presented 1 hour after ingesting 100 tablets of amantadine hydrochloride (100 mg/tab). Initial ECG revealed sinus tachycardia with a QRS of 113 msec, an R wave in lead aVR of 4–5 mm and a QTc of 526 msec. Her serum potassium was 3.0 mEq/L (3.0 mmol/L), her serum calcium was 9.4 mg/dl (2.35 mmol/L), and serum magnesium was 2.1 mg/dl (0.86 mmol/L) on labs drawn at initial presentation. The patient was intubated for airway protection, and her potassium was repleted and corrected over the next 9 hours. Her ECG abnormalities improved 8 hours after initial presentation and normalized at approximately 14 hours postingestion. The patient was discharged home 11 days after her ingestion. CONCLUSION: Acute amantadine toxicity manifests with life-threatening cardiotoxicity. Concurrent, often profound, hypokalemia may complicate the administration of sodium bicarbonate in the management of cardiac dysrhythmias.